Iron absorption stimulation by administration of soy protein hydrolysates containing bioactive peptides in rats - Ida Susanti; Noer Laily; Galih Kusuma Aji; Muhamaludin; Haris Muhamad Ikhsan (Current Research on Bioscences and Biotechnology, 2020)
The prevalence of iron deficiency anemia in Indonesia is high. Most of the anemia is caused by iron deficiency syndrome due to inadequate iron intake and low bioavailability of iron sources. Some studies indicated that bioactive peptides from certain protein hydrolysates could support iron absorption. Our previous study showed that soy protein hydrolysates containing bioactive peptides indicated an iron-binding activity and could increase its solubility in water. Aim of this study was to investigate the effect of soy protein hydrolysates administration on iron serum levels in anemic Sprague Dawley rats. Anemia induction was performed by applying NaNO2 (0.5 mg/ml per 200 g body weight (BW) of rats per day for 14 days) orally. The experiment was carried out in a completely randomized design, consisting of six groups. The first group was the control normal group (N), without induction and the others were treatment groups that were induced with NaNO2 and supplemented with iron (0.3 mg/200 g BW), consisted of control group (CMC), control iron (Fe) group, iron and soy protein hydrolysate-1 (270 mg/200 g BW) (FeSH-1) group, iron and soy protein hydrolysate-2 (270 mg/200 g BW) (Fe-SH2) group and positive control iron vitamin C (0.24 mg/200 g BW) (Fe Vit. C) group. The result showed that Fe-SH2 treatment group had a better iron-binding capacity rather than other groups. This result suggests that soy protein hydrolysates could enhance iron absorption, which might be applied in human as a functional food to reduce anemia prevalence.